1991
DOI: 10.1002/1097-0142(19911015)68:8<1770::aid-cncr2820680821>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of aneurysmal bone cyst, with an analysis of the literature

Abstract: An 11‐year‐old girl had a lytic, benign‐appearing, expansive lesion of the distal tibia radiologically interpreted as an aneurysmal bone cyst (ABC). Tissue from two extensive curettage procedures was also histologically diagnosed as ABC. Approximately 50 months after the onset of symptoms, and 28 months after her last curettage, a highly pleomorphic osteosarcoma developed. The patient had not received prior radiation therapy. The cases in the literature of possible malignant transformation of ABC are reviewed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 34 publications
1
40
0
4
Order By: Relevance
“…Options for treating ABCs have included simple curettage with or without bone grafting, complete excision, embolization, radiation therapy, or a combination of these methods [3,4]. Progression to malignancy has been described in the literature after treated with radiation therapy [6][7][8]. Although there are good results regarding the type of treatment, local recurrence has been described within all protocols of therapy and cannot be predicted.…”
Section: Introductionmentioning
confidence: 69%
“…Options for treating ABCs have included simple curettage with or without bone grafting, complete excision, embolization, radiation therapy, or a combination of these methods [3,4]. Progression to malignancy has been described in the literature after treated with radiation therapy [6][7][8]. Although there are good results regarding the type of treatment, local recurrence has been described within all protocols of therapy and cannot be predicted.…”
Section: Introductionmentioning
confidence: 69%
“…However, we found no reports of malignant transformation due to the use of PMMA. Some authors suggested that ABCs may occur per se as a secondary component of a prior lesion, either benign or malignant, that cannot be identified after the ABC has destroyed its architecture (Kyriakos and Hardy 1991). This additional fact could partly explain the malignant transformation of ABCs (Feigenberg et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Complications associated with ABCs in dogs include pathological bone fractures, recurrence, and malignant transformation (Barnhart 2002;Sarierler et al 2004). The same complications have been reported in humans, as well as surrounding bone-tissue invasion and metastasis (Kyriakos and Hardy 1991;Feigenberg et al 2001;Mendenhall et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations